(untitled) (ASEAN Engineering Journal, 2025)
The number of motor vehicle accidents keeps increasing from year to year. Based on Badan Pusat Statistik Indonesia in 2022, there are twenty-eight thousand people who died due to accidents. The number of accidents keeps increasing around 6.26% every year, which is most likely due to the escalation in the number of vehicles. The number of inter-city buses is growing around 2.23% every year. According to National Highway Traffic Safety Administration (NHTSA), most common type of accident that often occur on buses is frontal collisions. This accident can cause serious injuries or death because of impact on the passanger’s head. The severity of head injury can be calculated using Head Injury Criterion (HIC) which has several categories of injury consequences. The research is focused on sled test simulation by finite element method which uses acceleration data from Mihradi. The simulations are divided into three categories: chair with cushion, chair without cushion, and without front chair’s cushion. Each category has three subcategory of seatbelt system, namely lap seatbelt, lap and shoulder seatbelt, and without seatbelt. There are several conclusions from simulation’s result. First, the use of cushion can reduce HIC15 around 5.6% in comparison to no cushion case. Second, shoulder seatbelt is the safest type of seatbelt that can be used in bus. Third, the use of cushion changes the whole model dimension and change the dummy’s movement in front collision, which resulted in different value of HIC15 in comparison to case without cushion. Thus, cushion must be modelled in order to get accurate HIC15 values.